Endangered Heritage in the Islamic World: Islamic World Educational, Scientific and Cultural Organization (ICESCO) Emerging Role in Risk Mitigation and Cultural Resilience - Bilel Chebbi (Warisan: Journal of History and Cultural Heritage, 2025)
This article explores ICESCO’s evolving approach to protecting endangered heritage in the Islamic world since its restructuring in 2019. Employing a qualitative and interpretive design, the study analyzes organizational strategies, official reports, and secondary assessments, complemented by insights drawn from public presentations in Mosul, Sana’a, and Al-Quds. The research identifies a distinctive model of “southern heritage governance” that integrates rapid risk mitigation, community-driven recovery, and symbolic diplomacy. Through selected case vignettes, the article demonstrates how ICESCO combines technical conservation with local empowerment, climate-sensitive planning, and multi-scalar partnerships to confront challenges posed by armed conflict, urban degradation, and environmental pressures. Compared with UNESCO and ALECSO, ICESCO emerges as more agile and culturally embedded, though still limited by funding instability and restricted political access. The findings contribute to scholarly debates on heritage resilience by showing how culturally rooted institutions can reposition heritage as a resource for justice, healing, and identity, rather than solely for preservation. The article concludes with recommendations for scaling up risk mapping, enhancing youth engagement, and improving impact evaluation across member states.